2016
DOI: 10.1158/1078-0432.ccr-16-0493
|View full text |Cite
|
Sign up to set email alerts
|

FDA Approval of Palbociclib in Combination with Fulvestrant for the Treatment of Hormone Receptor–Positive, HER2-Negative Metastatic Breast Cancer

Abstract: On February 19, 2016, the FDA approved palbociclib (Ibrance, Pfizer) for use in combination with fulvestrant (Faslodex, AstraZeneca) for the treatment of women with hormone receptor (HR)-positive, HER2-negative advanced or metastatic breast cancer (MBC) with disease progression following endocrine therapy. The approval was based on the results of a randomized, double-blind, placebo-controlled trial conducted in 521 pre- and postmenopausal women with HR-positive, HER2-negative advanced or MBC. Patients were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
84
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(85 citation statements)
references
References 12 publications
0
84
0
1
Order By: Relevance
“…Single-agent palbociclib has failed to provide durable therapeutic response in various clinical trials (8,30), prompting a search for combinatorial approaches. The greatest success has emerged in combining CDK4/6 inhibitors with anti-estrogenic therapies in hormone-positive breast cancers (9). Given the regulatory role of the Ras pathway on the cell cycle, palbociclib has been studied in combination with MEK inhibitors against Ras-mutated tumors such as melanoma and pancreatic cancer (12,31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-agent palbociclib has failed to provide durable therapeutic response in various clinical trials (8,30), prompting a search for combinatorial approaches. The greatest success has emerged in combining CDK4/6 inhibitors with anti-estrogenic therapies in hormone-positive breast cancers (9). Given the regulatory role of the Ras pathway on the cell cycle, palbociclib has been studied in combination with MEK inhibitors against Ras-mutated tumors such as melanoma and pancreatic cancer (12,31).…”
Section: Discussionmentioning
confidence: 99%
“…It proved to be beneficial especially in tumors lacking p16INK4a or over-expressing cyclin D such as bladder and gastric cancers, while those without functional RB1 have been refractory to palbociclib treatment. Upon promising results in preclinical models of various cancers including GBM (6,7), palbociclib has been tested in several phase I/II clinical trials and has been approved by the FDA in combination with anti-estrogen therapies against hormone receptor-positive breast cancers (8,9). These clinical studies indicate that palbociclib as a single agent fails to provide durable responses, potentially due at least in part to tumor adaptation, and suggesting a need to combine with other agents.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proven that CCND1 and CDK4 played a vital role in BC (77,78). CDK4/6 inhibitors have shown great potential in preclinical studies and clinical trials, such as palbocilcib and ribociclib which has been applied in clinical (79,80). Though CDK4/6 inhibitors are mainly used to treat estrogen receptor (ER) + /HER2 -patients, some studies found that they also have potential therapeutic effect on ER + /HER2 + patients (81).…”
Section: Her2 Tk Inhibitorsmentioning
confidence: 99%
“…Palbociclib has received approval by the US Food and Drug Administration (FDA) and by the European Medicines Agency (EMA) for the treatment of hormone receptor-positive HER2-negative (HR+/HER2-) advanced breast cancer in combination with the hormonal treatments letrozole or fulvestrant [8,9], given the unprecedented results of three pivotal randomized clinical trials, the PALOMA-1, PALOMA-2 and PALOMA-3 [10,11,12]. PALOMA-1 and PALOMA-2 are phase II and phase III randomized trials, respectively, of palbociclib in combination with letrozole versus letrozole alone for previously untreated patients in the metastatic setting [10,11.]…”
Section: Cdk4/6 Inhibitorsmentioning
confidence: 99%